Modulation of adult hippocampal neurogenesis by interleukin 1 signaling - Maria I. Smirnova; Ning Quan (Neurobiology of Sleep and Circadian Rhythms)
Adult hippocampal neurogenesis (AHN) plays a critical role in cognition and emotional regulation. Recent studies have linked compromised AHN to numerous neurological and psychological disorders. The actions of the inflammatory cytokine interleukin-1 (IL-1) have been found to suppress AHN and antagonism of IL-1 signaling has been advocated as a therapeutic strategy for the treatment of neurodegenerative diseases and affective disorders. On the other hand, work from Jim Krueger's group revealed the physiological function of IL-1 in brain homeostasis, indicating the potential downside of IL-1 blockade. Current literature also shows AHN participates in normal functions of the brain in parallel to IL-1. This mini-review analyzes how IL-1 might positively or negatively modulate AHN and the implications of the relationship between IL-1 and AHN on health and disease. Specifically, we will highlight the parallels between IL-1 signaling and AHN in physiological and disease states. We propose that IL-1 signaling modulates AHN in a context-dependent manner; whereas its elevated signaling impairs neurogenesis and contributes to neurological and psychiatric disorders, its physiological role suggests potential therapeutic benefits of IL-1 antagonism must consider the preservation of the beneficial actions of IL-1.